Teaching High-Value Care: Case Vignettes for Pediatric Practice - Lauren LaRue Walker; Akshata Hopkins; Sahar Nayereh Rooholamini; Corrie McDaniel; Yemisi Jones; Lisa E. Herrmann; Vivian Lee; Francine Bynum; Michael Tchou; Jimmy Beck (Association of American Medical Colleges, 2018)
Introduction As health care systems recognize the importance of high-value care (HVC), physicians must focus on individualized patient outcomes using economically responsible and evidence-based medicine. The best ways to teach medical trainees HVC principles that can result in meaningful practice and behavior changes are unknown. Methods We designed a case-based curriculum mapping six common pediatric clinical scenarios to HVC principles. Each scenario included learning objectives, small-group activities, educational resources, a facilitator guide, and participant evaluations. After internal and external review, the scenarios were piloted at four teaching institutions (Children's Hospital Los Angeles, Johns Hopkins All Children's Hospital, Seattle Children's Hospital, and Texas Children's Hospital). Facilitators were encouraged to adapt each vignette to learner needs and site-specific conference characteristics. All participants were asked to complete anonymous case-specific evaluations at the end of each session. Results Approximately 331 individuals (students, residents, attendings) participated, with an evaluation response rate of 76% (n = 253). Participants across all sites acknowledged the sessions as a valuable use of time (range: 4.2-4.6 on a 5-point Likert scale) and identified HVC principles that could be applied daily in clinical practice (range: 4.4-4.6). Discussion Implementation of six case-based HVC vignettes at four pilot institutions was both feasible and well received by a diverse group of learners. The curriculum was perceived as valuable and applicable to learners' clinical practice. Next steps include longitudinal assessments of learners and the development of tools measuring HVC-related behaviors to understand better the impact of the curriculum on clinical practice.